The safety critical systems handbook : a straightforward guide to functional safety: IEC 61508 (2010 edition), IEC 61511 (2016 edition) & related guidance, including machinery and other industrial sectors - Smith, David J. 1943 June 22-; Simpson, Kenneth G. L. (Butterworth-Heinemann is an imprint of Elsevier, 2016)
The Safety Critical Systems Handbook: A Straightforward Guide to Functional Safety: IEC 61508 (2010 Edition), IEC 61511 (2016 Edition) & Related Guidance, Fourth Edition, presents the latest on the electrical, electronic, and programmable electronic systems that provide safety functions that guard workers and the public against injury or death, and the environment against pollution. The international functional safety standard IEC 61508 was revised in 2010, and authors David Smith and Kenneth Simpson provide a comprehensive guide to the revised standard, as well as the revised IEC 61511 (2016). The book enables engineers to determine if a proposed or existing piece of equipment meets the safety integrity levels (SIL) required by the various standards and guidance, and also describes the requirements for the new alternative route (route 2H), introduced in 2010. A number of other areas have been updated by Smith and Simpson in this new edition, including the estimation of common cause failure, calculation of PFDs and failure rates for redundant configurations, societal risk, and additional second tier guidance documents. As functional safety is applicable to many industries, this book will have a wide readership beyond the chemical and process sector, including oil and gas, machinery, power generation, nuclear, aircraft, and automotive industries, plus project, instrumentation, design, and control engineers.
Includes index.
Keywords: Industrial safety -- Standards -- European Union countries -- Handbooks, manuals, etc.; Process control -- Standards -- European Union countries -- Handbooks, manuals, etc.; Manufacturing processes -- Safety measures -- Standards -- European Union countries -- Handbooks, manuals, etc.; elektronické knihy; electronic books